Recent advances in soft functional materials: preparation, functions and applications - Li, Jun; Wong, Wai-Yeung; Tao, Xiao-ming (Nanoscale, 2020)
Synthetic materials and biomaterials with elastic moduli lower than 10 MPa are generally considered as soft materials. Research studies on soft materials have been boosted due to their intriguing features such as light-weight, low modulus, stretchability, and a diverse range of functions including sensing, actuating, insulating and transporting. They are ideal materials for applications in smart textiles, flexible devices and wearable electronics. On the other hand, benefiting from the advances in materials science and chemistry, novel soft materials with tailored properties and functions could be prepared to fulfil the specific requirements. In this review, the current progress of soft materials, ranging from materials design, preparation and application are critically summarized based on three categories, namely gels, foams and elastomers. The chemical, physical and electrical properties and the applications are elaborated. This review aims to provide a comprehensive overview of soft materials to researchers in different disciplines. This review discusses the recent progress of three kinds of soft materials, namely gels, foams and elastomers, with emphasis on materials, properties and applications in flexible sensors, soft actuators, energy convention and storage.